Dombeya scorpioides (Malvaceae: Dombeyoideae), a new species from southeastern Madagascar - Fievet, Lucile Jourdain; Pechon, Timothee Le; Dubuisson, Jean-Yves; Applequist, Wendy (Phytotaxa, 2025)
Dombeya scorpioides, a new endemic species of Dombeya (Malvaceae) from southeastern Madagascar, is described. Morphological analysis places this species within Dombeya section Xeropetalum as defined by Arènes. The species is distinguished by its unique biparous cyme, unusually elongated with mostly scorpioid terminal units. It is further differentiated from other species with similar narrow leaves by its hispid ovary with well-developed stellate hairs. Due to its restricted geographic distribution and past and future threats to its habitat, this species should be classified as Endangered according to IUCN Red List Criteria.